Actin-rich lamellipodia-like protrusions contribute to the integrity of epithelial cell-cell junctions - Senju, Yosuke; Mushtaq, Toiba; Vihinen, Helena; Manninen, Aki; Saarikangas, Juha; Ven, Katharina; Engel, Ulrike; Varjosalo, Markku; Jokitalo, Eija; Lappalainen, Pekka (The journal of biological chemistry, 2023)
Metastasis-suppressor 1 (MTSS1) is a membrane-interacting scaffolding protein that regulates the integrity of epithelial cell-cell junctions and functions as a tumor suppressor in a wide range of carcinomas. MTSS1 binds phosphoinositide-rich membranes through its I-BAR domain and is capable of sensing and generating negative membrane curvature in vitro. However, the mechanisms by which MTSS1 localizes to intercellular junctions in epithelial cells and contributes to their integrity and maintenance have remained elusive. By carrying out EM and live-cell imaging on cultured Madin-Darby canine kidney cell monolayers, we provide evidence that adherens junctions of epithelial cells harbor lamellipodia-like, dynamic actin-driven membrane folds, which exhibit high negative membrane curvature at their distal edges. BioID proteomics and imaging experiments demonstrated that MTSS1 associates with an Arp2/3 complex activator, the WAVE-2 complex, in dynamic actin-rich protrusions at cell-cell junctions. Inhibition of Arp2/3 or WAVE-2 suppressed actin filament assembly at adherens junctions, decreased the dynamics of junctional membrane protrusions, and led to defects in epithelial integrity. Together, these results support a model in which membrane-associated MTSS1, together with the WAVE-2 and Arp2/3 complexes, promotes the formation of dynamic lamellipodia-like actin protrusions that contribute to the integrity of cell-cell junctions in epithelial monolayers.
Online verfügbar: 3. März 2023, Artikelversion: 27. April 2023
Gesehen am 10.08.2023